A Monte Carlo approach for assessing the specificity of protein oligomers observed in nano-electrospray mass spectra - Lane, L; Ruotolo, B; Robinson, C; Favrin, G; Benesch, J (2009)
Nano-electrospray mass spectrometry is an emerging approach for studying the architecture and dynamics of complex oligomeric proteins. The analysis of such species can, however, be hindered by 'non-specific' protein-protein associations which arise as a result of the electrospray method. To understand the formation of specific versus non-specific protein oligomers detected by mass spectrometry we have developed a simple and rapid computational approach. This Monte Carlo algorithm characterizes the occupancy of protein species in the last offspring droplets created by the nano-electrospray process. As such it enables us to assess whether oligomers detected in mass spectra reflect solution populations, or instead are the result of associations during droplet fission and evaporation. We have trained and validated this method on three model protein complexes which are not known to form higher order oligomers, and one which has a tendency to self-associate in solution in a concentration dependent manner. We have then compared predictions of droplet occupancy to abundances obtained from mass spectra for the tetrameric amyloid-related protein transthyretin, which can cause cardiomyopathy and polyneuropathy in humans. Interestingly, when such comparisons were made for wild-type transthyretin we were able to observe a propensity for the protein to form specific oligomers larger than the tetramer. In contrast, the tendency for the leucine-55-proline variant to form such oligomers was considerably reduced. We contemplate the significance of these specific higher order wild-type oligomers, and absence of such species in the variant, on the pathway of amyloid formation in transthyretin. More generally this easy-to-implement computational approach promises to improve our ability to identify oligomers of biological significance within the mass spectra of heterogenous protein complexes. © 2009 Elsevier B.V. All rights reserved.